Impacts of different ENSO flavors and tropical Pacific convection variability (ITCZ, SPCZ) on austral summer rainfall in South America, with a focus on Peru - Sulca, Juan (2017)
El Niño in the eastern and central Pacific has different impacts on the rainfall of South America, and the atmospheric pathways through the South Pacific Convergence Zone (SPCZ) and Inter-Tropical Convergence Zone (ITCZ) are poorly understood. To address this, we performed linear regression analysis of E (eastern Pacific) and C (central Pacific) indices of sea surface temperature (SST), as well as precipitation indices for the SPCZ and ITCZ, with gridded precipitation and reanalysis data sets during the austral summer (December–February) for the 1980–2016 period.